Pengembangan Bahan Ajar Modul Pendidikan Agama Katolik Berbasis Moral Reasoning - Sunaryo, Andreas; Ananda, Nandang Kosasih; Herpratiwi, Herpratiwi (Indonesia Journal of Educational Technology, 2018)
The purpose of this study is to describe: 1) the condition of existing teaching materials and the potential of teaching materials to be developed, 2) effectiveness, 3) efficiency, and 4) attractiveness. This research approach uses Research and Development. The research was conducted at SMA Xaverius Pahoman, SMA Xaverius Pringsewu and SMU Bhakti Baradatu. Data collection uses observation, unstructured interviews, questionnaires and tests. Data were analyzed statistically descriptive and n-Gain. The conclusions of this study are: 1) the learning condition is still teacher-centered, the characteristics of students aged 15-17 years are less motivated to learn to use book learning resources, so that the potential to be developed in the form of module teaching materials. 2) effective module product with category index gain high, everage value of n-Gain experimental class 14,91> control class 14, 71. 3) efficient use of module used in learning, with efficiency values of 1,5. 4) The appeal of modules in the category of interest (88.85%).Tujuan penelitian ini adalah mendeskripsikan : 1) kondisi bahan ajar yang ada dan potensi bahan ajar yang akan dikembangkan, 2) efektifitas, 3) efisiensi, dan 4) kemenarikan. Pendekatan penelitian ini mengunakan Penelitian dan Pemgembangan. Penelitian dilakukan di SMA Xaverius Pahoman, SMA Xaverius Pringsewu dan SMU Bhakti Baradatu. Pengumpulan data mengunakan observasi, wawancara tidak terstruktur, angket dan tes. Data dianalisis secara statistik deskriptif dan n-Gain. Kesimpulan dari penelitian ini adalah : 1) kondisi pembelajaran masih berpusat pada guru, karakteristik siswa usia 15-17 tahun kurang termotivasi untuk belajar menggunakan sumber belajar buku paket, sehingga berpotensi untuk dikembangkan bahan ajar berupa modul . 2) produk modul efektif dengan kategori tinggi, nilai n-Gain kelas eksperimen 14.91> kelas kontrol 14,71. 3) penggunaan modul efisien digunakan dalam pembelajaran, dengan nilai efisiensi 1,5. 4) Daya tarik modul dalam kategori menarik (88,85%).Kata Kunci : bahan ajar, modul, moral reasoning